Vaginisenegalia massiliensis gen. nov., sp. nov., a new bacterium isolated from the vagina flora and its taxono-genomic description. (November 2019) - Lo, C.I.; Fall, N.S.; Fadlane, A.; Armstrong, N.; Fournier, P.-E.; Sokhna, C.; Raoult, D.; Fenollar, F.; Lagier, J.-C.
Abstract: Strain Marseille-P5643 T was isolated from a vaginal sample of a healthy Senegalese woman. It is an anaerobic Gram-negative, rod-shaped bacterium. Strain Marseille-P5643 T exhibits 93.7% similarity levels with the Facklamia hominis strain ATCC 700628 T, the phylogenetically closest related species with standing in nomenclature. The draft genome size of strain Marseille-P5643 T is 1.79 Mb with 39.0 mol% of G+C content. We propose here the creation of Vaginisenegalia massiliensis gen. nov., sp. nov., as a new bacterial genus from the phylum Firmicutes.